Implementasi Metode Fuzzy Pada Kualitas Air Kolam Bibit Lele Berdasarkan Suhu Dan Kekeruhan - Muchammad Cholilulloh; Dahnial Syauqy; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Improper pool water quality can cause fish health will be disturbed, fish growth will be slow and can threaten crop failure. Factors that may affect water quality include temperature and turbidity. Water temperature for catfish seed cultivators ranges from 23ËšC - 30ËšC and turbidity of water can be seen from the clarity of water based on the color. Cloudy color on the water causes the reflection of the sun can not get into the water. Whereas in the process of growth of catfish seedlings needed enough sunlight. In this research used fuzzy takagi-sugeno method to measure water quality at catfish seed pool based on temperature and turbidity. Parameters in use there are two temperature parameters and turbidity sensor. The output of this research is the pump control that serves to replace or fill the pond water. The pond water will be replaced when it has passed the turbidity range limit and fill it if it exceeds the range of cold or hot temperature that has been determined. Based on the results of testing this system can read the value of temperature with an average yield of 2.39% and turbidity value can measure the level of water concentration, and can control the quality of water well